1980
DOI: 10.2190/ngub-v4rm-t7dc-xth3
|View full text |Cite
|
Sign up to set email alerts
|

DPT as an Adjunct in Brief Psychotherapy with Cancer Patients

Abstract: Thirty cancer patients suffering from psychological distress participated in a pilot project of individual psychotherapy that offered – over a four week period of time – approximately twelve hours of conventional verbal interaction and a single intensive drug-assisted therapy session that employed dipropyltryptamine (DPT), a short-acting psychedelic drug. The efficacy of the total therapeutic approach in enhancing the quality of life is indicated by the analysis of data from psychological tests and independent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…Since then, the scientific investigation into psychotherapeutic uses of psychedelic drugs has been conducted in many countries and resulted in the release of dozens of books and more than 1000 peerreviewed clinical papers reporting the use of psychedelic substances administered to more than 40,000 subjects (Dyck, 2005;Grinspoon & Bakalar, 1979;Passie, 1997). Numerous clinical research studies of the subjects treated with psychedelic compounds, performed from the late 1950s through the present time, repeatedly demonstrated sometimes impressive treatment outcomes (e.g., Grob, 1998Grob, , 2002Grof, 1980;Grinspoon & Bakalar, 1979;Kolp et al, 2006Kolp et al, , 2007Kolp et al, , 2009Pahnke, 1968Pahnke, , 1969Pahnke, Kurland, Unger, Savage, & Grof, 1970;Pahnke, Kurland, Unger, Savage, Wolf, & Goodman, 1970;Pahnke, McCabe, Olsson, Unger, & Kurland, 1969;Richards, 1979Richards, /1980Richards, Grof, Goodman, & Kurland, 1972;Richards et al, 1979;Richards, Rhead, DiLeo, Yensen, & Kurland, 1977;Walsh & Grob, 2005;Watts, 1973;Yensen & Dryer, 1993.…”
Section: International Journal Of Transpersonal Studies 97mentioning
confidence: 91%
See 1 more Smart Citation
“…Since then, the scientific investigation into psychotherapeutic uses of psychedelic drugs has been conducted in many countries and resulted in the release of dozens of books and more than 1000 peerreviewed clinical papers reporting the use of psychedelic substances administered to more than 40,000 subjects (Dyck, 2005;Grinspoon & Bakalar, 1979;Passie, 1997). Numerous clinical research studies of the subjects treated with psychedelic compounds, performed from the late 1950s through the present time, repeatedly demonstrated sometimes impressive treatment outcomes (e.g., Grob, 1998Grob, , 2002Grof, 1980;Grinspoon & Bakalar, 1979;Kolp et al, 2006Kolp et al, , 2007Kolp et al, , 2009Pahnke, 1968Pahnke, , 1969Pahnke, Kurland, Unger, Savage, & Grof, 1970;Pahnke, Kurland, Unger, Savage, Wolf, & Goodman, 1970;Pahnke, McCabe, Olsson, Unger, & Kurland, 1969;Richards, 1979Richards, /1980Richards, Grof, Goodman, & Kurland, 1972;Richards et al, 1979;Richards, Rhead, DiLeo, Yensen, & Kurland, 1977;Walsh & Grob, 2005;Watts, 1973;Yensen & Dryer, 1993.…”
Section: International Journal Of Transpersonal Studies 97mentioning
confidence: 91%
“…Psychedelic therapy involves the use of higher doses of hallucinogenic drugs, with the aim of inducing ego-dissolving transpersonal (e.g., transcendental, mystical, spiritual) peak experiences (Grinspoon & Bakalar, 1979;Grob, 1998Grob, , 2002Grof, 1978Grof, , 1980Grof, , 1986Grof & Halifax, 1976;Grof, Goodman, Richards, & Kurland, 1973;Pahnke, 1968;Richards et al, 1972Richards et al, , 1977Richards et al, , 1979Walsh & Grob, 2005;Watts, 1973;Yensen & Dryer, 1993. This method was initially developed by Hoffer and Osmond in the United States (Hoffer, 1967).…”
Section: International Journal Of Transpersonal Studies 97mentioning
confidence: 99%
“…Anecdotal observations and non-blind studies in cancer patients suffering from anxiety and depression suggested that LSD administration resulted in an ability to openly discuss existential fears and be at peace with approaching death, and that this reorientation often outlasted the acute drug effects (Kast and Collins, 1964; Cohen, 1965; Kast, 1967). Follow up investigations involved the administration of a high dose of a hallucinogen to carefully prepared patients under highly supportive interpersonal conditions, with the patient wearing eyeshades and listening to classical music through headphones during the course of pharmacological action, a model known as “psychedelic peak therapy” or “psychedelic therapy” (Kurland et al, 1969; Pahnke et al, 1969; Richards et al, 1972; Grof et al, 1973; Kurland et al, 1973; Grof and Halifax, 1977; Richards et al, 1977; Richards et al, 1979; Grof, 1980; Richards, 1980; Kurland, 1985). Unfortunately, these early studies did not include the stringent control conditions or groups that now have become standard in modern clinical psychopharmacology research.…”
Section: Relevant Historymentioning
confidence: 99%
“…Numerous clinical research studies of terminallyill patients (e.g., with end-stage cancer) treated with psychedelic compounds (i.e., primarily lysergic acid diethylamide [LSD]) were performed from the late 1950s to the early 1970s and sometimes demonstrated remarkably impressive treatment outcomes (e.g., Bakalar, 1979;Richards, 1979Richards, /1980Grof, 1980;Yensen & Dryer, 1993/1994Grob, 1998Grob, , 2002Walsh & Grob, 2005). Kast pioneered pain treatment with LSD in patients with terminal cancer by discovering that low dose LSD (100 micrograms) brought greater analgesia than more widely used medication (such as Dilaudid [hydromorphone] and Demerol [meperidine]) and that these superior effects lasted for several days as opposed to several hours; in addition, he and colleagues documented diminished fear of death and significant reduction of depressive symptoms (Kast, 1962(Kast, , 1966a(Kast, , 1966bKast & Collins, 1964).…”
Section: Introductionmentioning
confidence: 99%